2021
DOI: 10.1016/j.jpeds.2021.01.065
|View full text |Cite|
|
Sign up to set email alerts
|

Stratification of Culture-Proven Early-Onset Sepsis Cases by the Neonatal Early-Onset Sepsis Calculator: An Individual Patient Data Meta-Analysis

Abstract: Objectives To provide a comprehensive assessment of case stratification by the Neonatal Early-Onset Sepsis (EOS) Calculator, a novel tool for reducing unnecessary antibiotic treatment.Study design A systematic review with individual patient data meta-analysis was conducted, extending PROS-PERO record CRD42018116188. Cochrane, PubMed/MEDLINE, EMBASE, Web of Science, Google Scholar, and major conference proceedings were searched from 2011 through May 1, 2020. Original data studies including culture-proven EOS ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 32 publications
(38 reference statements)
2
23
0
Order By: Relevance
“…NICU stay. Additionally, in contrast to the paper by Escobar et al 52 reporting on the benefits of using an EOS calculator, a recent systematic review including over 459,000 infants found limited evidence in this regard. Although this may highlight the importance of continuous CDSA development, it also raises concerns about overfitting and the generalisability of CDSA findings to external settings.…”
Section: Implication For Daily Clinical Carementioning
confidence: 80%
“…NICU stay. Additionally, in contrast to the paper by Escobar et al 52 reporting on the benefits of using an EOS calculator, a recent systematic review including over 459,000 infants found limited evidence in this regard. Although this may highlight the importance of continuous CDSA development, it also raises concerns about overfitting and the generalisability of CDSA findings to external settings.…”
Section: Implication For Daily Clinical Carementioning
confidence: 80%
“…25 Our results also correspond to those of a recent meta-analysis on 234 EOD patients, which reported that the EOSC recommends antibiotics in 41% of EOD patients shortly after birth. 15 The EOSC relies more heavily on signs of clinical illness, resulting in a more specific approach and a substantial reduction in unnecessary EOD treatments. This comes at the expense of sensitivity, as can be expected.…”
Section: Discussionmentioning
confidence: 99%
“… 25 Our results also correspond to those of a recent meta-analysis on 234 EOD patients, which reported that the EOSC recommends antibiotics in 41% of EOD patients shortly after birth. 15 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the sepsis calculator is highly dependent on clinical observation, it is similar to a population preselected by healthcare workers using serial examinations. 33 Studies of approaches using serial examinations are increasingly conducted, with promising results. 24,25,27 This approach may be combined with our new model as well.…”
Section: Discussionmentioning
confidence: 99%